La Efectividad de la Ayuda Externa en Bolivia - Lykke E. Andersen; José Luis Evia (Institute for Advanced Development Studies (INESAD), 2003)
– This document investigates the effectiveness of foreign aid in Bolivia. When comparing accumulated aid in each sector during the period 1998-2002 with the progress in each sector during the same period, it becomes clear that the four sectors receiving by far the most aid (Institutional strengthening, Rural Development, Roads, and Budget support) have shown disappointingly little progress. When the impact of aid is analyzed in a computable general equilibrium model, it becomes clear that aid tends to have a positive effect on growth, but only in the short run, and it tends to have an adverse effect on the income distribution.
Keywords: F35; 330; Efectividad; Ayuda extera; Bolivia